The impact of social media marketing on political brand equity - Razak, Nur Amirah (2013)
The theory of Brand Equity has been studied intensively by researchers, stemming from its applicability on everyday consumer goods to the services industry. In recent years, the growth of social media has offered companies new ways of understanding the development of Brand Equity. It is without a doubt the social media have grown exponentially and it is said to be the next media for marketing [Yan, 2011]. At the same time, there has been a growing interest in applying marketing concepts to political parties. The idea of this application, however, is a challenging assertion to make. On the basis of several empirical studies, this study aims to gain an understanding on the effects of social media marketing on a political brand, given the landscape of Singapore’s political environment.